(untitled) (Research, Society and Development, 2020)
Introduction: The most common complication resulting from bilateral sagittal split osteotomy in orthognathic surgery to reposition the mandible in relation to the skull base is the possible damage to the lower alveolar nerve, causing paresthesia in the region of the lower lip and tip of the chin. The incidence of paresthesia after performing this technique is 85-87% of cases. Throughout history, many treatments aimed at restoring sensorineural function in this area have been reported. One of the fields that is currently growing is low power laser therapy. Objective: The aim of this study was to review the literature on the use of laser therapy in the postoperative period of bilateral sagittal osteotomies of the mandibular branch. Methodology: The articles were selected using the PubMed database. For inclusion criteria of the article it should be published in English and whose adopted methodology would allow obtaining significant evidence. Results: The main results found were that low-level laser therapy is effective in helping to control postoperative pain as well as speeding up the repair and regeneration process of tissues, especially nerves, thus reducing postoperative paresthesia. Conclusion: It is concluded that low-power laser therapy is beneficial in accelerating tissue repairs, bringing greater comfort to the patient. However, further studies and follow-up are needed in this area in order to establish a complete application protocol.